PLD3 Rare Variants Identified in Late-Onset Alzheimer’s Disease Affect Amyloid-β Levels in Cellular Model - Tan, Mengshan; Li, Jieqiong; Ma, Fangchen; Zhang, Xing; Zhao, Qingfei; Cao, Xipeng (Frontiers in Neuroscience, 2019)
Next-generation sequencing studies have reported that rare variants in PLD3 were associated with increased risk of late-onset Alzheimer’s disease (LOAD) in European cohorts. The association has been replicated in a Han Chinese cohort, two rare variants p.I163M in exon7 and p.R356H in exon11 of PLD3 were found to be associated with LOAD risk. Whether these variants have deleterious effects on protein function, and the underlying mechanisms by which they influence LOAD pathogenesis are unknown. Our results are the first to validate the hypothesis that these variants could lead to reduced PLD3 activity and affect amyloid-β levels in cellular model of AD, possibly via autophagy-dependent mTOR signaling pathway, indicating that PLD3 may represent a new therapeutic target for AD.